Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi Pada 19 Kabupaten dan Kota di Sumatera Barat Tahun 2019-2021 - Vivi Oktavia; Dewi Zulvia (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Economic growth is an illustration of the existence of economic development in an area, therefore the government always strives for economic growth to increase from year to year which will improve people's welfare. This study aims to determine the effect of regional original income (X1) and balancing funds (X2) on economic growth (Y) in 19 districts and cities in West Sumatra in 2019-2021. This research uses a quantitative method. Data processing uses the Eviews (2023) application. The results of this study can be concluded that regional original income (X1) has no effect on economic growth (Y) and balance funds (X2) have a positive and significant effect on economic growth (Y) in 19 regencies and cities in West Sumatra in 2019-2021.